Exploring Children’s Literature for Freirean Themes of Dialogue and Humanization : A Narrative and Multimodal Discourse Analysis - Uppala, Krishna (My University, 2025)
Children’s literature has been acknowledged to have the capability to critically challenge the status quo by incorporating counter-narratives that critically question mainstream representations of dominant groups. Freirean critical pedagogy connects this questioning of privilege with an orientation towards action from the reader through reading the word and the world. The concepts of dialogue and humanization provide a structure for analyzing the potential for the use of children’s books as a point of departure for a critical pedagogy. The purpose of this study is to analyze children’s books to determine whether and how they are characterized by these concepts of Freirean critical pedagogy. This study examines the questions of how relationships are constructed in the selected books through the interpersonal metafunction of discourse and how these relationships characterized Freirean concepts of horizontal relationships and humanization. In this study, the analysis is done on selected Newbery award winning children’s books. The study employed narrative discourse analysis for analyzing books predominantly in textual mode and multimodal discourse analysis for texts that included texts and images equally. Findings indicate that the books were characterized by Freirean concepts of dialogue through representations of horizontal relationships between friends and family. The relationship between the readers and the characters was also generally equal, which ensured that readers engaged with the issues the characters faced. The books characterized humanization through positioning the antagonist within structural inequalities, highlighting the problems rather than the oppressors or the victims. Praxis is highlighted through the centering of problems in the narratives, contextual solutions to which are arrived at through the agency of the characters involved. This research indicates that children’s books can offer multiple points of entry into critical pedagogy including problem-posing education, peace education and multicultural education by advocating for connecting the reading of the book to actions of social justice within their communities.
Keywords: Children’s Literature, Critical pedagogy, dialogue, humanization, praxis